A Thematic Analysis of Beauty Influencers Narrative Strategies on Instagram From the Audience's Perspective - Jacub, Evelyne Trisa Diandra (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Instagram has become a primary platform for beauty influencers to build connections with their audiences through engaging narrative strategies. This study examines the narrative techniques employed by beauty influencers on Instagram and explores how audiences respond to these elements. Using a thematic analysis approach, the study examines narrative elements such as story personalization, content authenticity, and value relevance. This study employs a qualitative approach to explore and understand the experiences of Instagram users who follow beauty influencers. Data collection was conducted through in-depth interviews with three active followers of beauty influencers on Instagram. Through thematic analysis, the findings indicate that narrative elements such as coherence and fidelity are instrumental in shaping audience perceptions, fostering trust, and influencing purchase decisions related to promoted products. Narrative strategies that emphasize honesty, cultural relevance, and real experiences foster stronger emotional connections between influencers and their audiences. Moreover, visually driven narratives, such as before-and-after videos and product journey content, are particularly effective in building trust and enhancing the impact of digital marketing efforts. This research underscores the importance of a narrative approach in building emotional connections between brands, influencers, and audiences. By understanding the effective elements of narrative strategies, marketers can create campaigns that are more relevant, authentic, and impactful in the digital era.